2019
DOI: 10.1017/s0305000918000569
|View full text |Cite
|
Sign up to set email alerts
|

Visual sequential processing and language ability in children who are deaf or hard of hearing

Abstract: This study investigated the role of sequential processing in spoken language outcomes for children who are deaf or hard of hearing (DHH) ages 5;3 – 11;4 by comparing them to children with typical hearing (TH), ages 6;3 – 9;7, on sequential learning and memory tasks involving easily nameable and difficult-to-name visual stimuli. Children who are DHH performed more poorly on easily nameable sequencing tasks, which positively predicted receptive vocabulary scores. Results suggest sequential learning and memory ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Studies have suggested that the linguistic variability shown by deaf children might result from a deficit in their implicit learning skills [18,20,21]. However, several studies have presented data that challenge this hypothesis [23][24][25][26][27], thereby creating a vibrant theoretical and methodological debate in this area of research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have suggested that the linguistic variability shown by deaf children might result from a deficit in their implicit learning skills [18,20,21]. However, several studies have presented data that challenge this hypothesis [23][24][25][26][27], thereby creating a vibrant theoretical and methodological debate in this area of research.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain optimal performance in the DTP task, children needed to adjust their motor preparation in terms of response speed. In sum, compared to previous implicit learning tasks that focused on learning the elements that comprise a sequence [20,21,[23][24][25][26][27], here we were interested in investigating whether deaf children are able to learn the temporal structure of a sequence of imperative stimuli and adjust their motor behaviour accordingly. Based on the results obtained by previous studies involving the DTP task [32], we expect that children who are able to learn implicitly the temporal distribution of the stimuli in each block will perform better than children who are not.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here also, the correlations with language outcomes seem relatively low and somewhat inconsistent. Gremp, Deocampo, Walk, and Conway () found correlations between visual sequential processing and vocabulary size among deaf children ( r = .29, p = .014), but not among hearing children (see also Conway et al., ). In contrast, Clark and Lum () found a significant correlation between SRT performance and grammatical processing speed (measured using a picture matching task), for hearing children, but not deaf ones.…”
Section: The Predictive Relation Of Implicit Statistical Learning To mentioning
confidence: 94%